Ketamine Infusion Used to Successfully Control Refractory Status Epilepticus in a Pregnant Patient - Murad Talahma; Vivek Sabharwal; Yana Bukovskaya; Fawad Khan (Case Reports in Neurological Medicine)
The management of SE during pregnancy is especially challenging to the treating physician. While antiepileptic medications might cause teratogenicity, SE can have significant morbidity and mortality on both the mother and the developing fetus. This case report demonstrated the successful use of ketamine infusion in the management of RSE in pregnancy without affecting the immediate outcome of pregnancy. The fetus survived this complicated ICU stay and outpatient follow-up was generally uncomplicated. The pregnancy was ended with a delivery of a normal female newborn.